The Effectiveness of Problem-Based Electronic Worksheet to Increase Student Creativity in Hooke’s Law - I Dewa Putu Nyeneng; Reza Afrian Yudha; Hervin Maulina (Jurnal Pembelajaran Fisika, 2021)
This study aims to determine the effectiveness of problem-based electronic worksheets to increase students’ creativity in Hooke's law at SMAN 2 Bandarlampung. The population is all students of class XI MIPA, and the sample is 20 student of XI MIPA 4, with group pretest-posttest research design. The data analysis techniques used are normality test, paired sample t-test, N-Gain test, and effect size test. The difference between the average pretest and posttest is 7.4. The N-Gain score obtained is 0.2 with low criteria. The results of the effect size test obtained a score of 0.8 with the criteria of having a large effect. Based on the results of the study, it can be concluded that problem-based electronic worksheets can increase student’s creativity.Keywords: problem-based electronic worksheets, hooke’s law, student’s creativityDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202105